Language games in the Dayak tribe: a study of meaning and language structure - Triyoga, Anwar Ibrahim; Mubarok, Ahmad; Purwanti, Purwanti (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
This study examines the dynamics of language use, particularly the Dayak Maanyan language in Kalimantan, using the framework of language games in Wittgenstein's philosophy of language. This study focuses on analyzing the orientation of thought in the use of the Dayak Maanyan language, outlining the rules of games in its expressions, and evaluating the compatibility of Wittgenstein's concept of language games with the Dayak Maanyan language. Utilizing a qualitative approach through literature studies, data were collected from various relevant scientific publications on the Dayak language and culture, as well as Wittgenstein's theory of language games. The findings reveal that the Dayak Maanyan language, through its diverse dialects and communicative practices, serves not only as a tool for communication, but also as a medium for strengthening social identity and preserving cultural traditions. This language reflects the cultural values and social structures of the Dayak community, in which the meaning of language emerges from its contextual use in daily life and specific social practices. These results align with Wittgenstein's philosophical concept, which emphasizes that meaning arises from use. This study contributes to a deeper understanding of the relationship between language, meaning, and social practices in multicultural societies, particularly in the Dayak community.